Giant Cell Tumor of Soft Tissue—A Rare Cause of Mass in the Liver: A Case Report - Chen, Piaopiao; Hu, Qiang; Wu, Jinfeng (Frontiers in Surgery, 2022)
Primary giant cell tumors of soft tissues (GCT-STs) are extremely rare soft tissue tumors, located both in superficial and deep soft tissues. Clinically, GCT-ST manifests as a slow-growing, well-defined, painless mass. We report a case of an 88-year-old female patient with upper abdominal distension, fever, and anemia. Laparoscopic exploration revealed that a tumor located in the left lobe of liver with localized rupture and hemorrhage. Postoperative pathology revealed that the tumor was composed of monocytes and osteoclast-like multinucleated giant cells, accompanied by extensive hemorrhage and necrosis, as well as cytologic atypia. Since mitotic cells are difficult to be detected in pathological diagnosis, combined with immunohistochemistry, the tumor was diagnosed as a giant cell tumor of soft tissue. This case report highlights the primary choice of histology and immunohistochemistry for the correct diagnosis of GCT-ST since preoperative radiological diagnosis is nonspecific and prone to mistake.